On Two Hypotheses in Economic Analysis of Stochastic Processes - ENDOVITSKY, Dmitry Aleksandrovich; DAVNIS, Valery Vladimirovich; KOROTKIKH, Viacheslav Vladimirovich (Journal of Advanced Research in Law and Economics; Vol 8 No 8 (2017): JARLE, Volume VIII, Issue 8(30), Winter 2017DO - 10.14505//jarle.v8.8(30).09, 2018)
Purpose: Development of the apparatus of the stochastic processes econometric modeling. Discussion: The authors identify risk component in the dynamics of stochastic processesin the economy. Theoretical justification of the alternative and proportional expectations is usedto make probabilistic nature of the risk. Results: The authors suggest stochastic process decomposition based on econometric approach to allocate a probability space of risks, and to identify shocks realizations that lie beyond the boundary of this space. Proportional expectations hypothesis distinguished two types of the event influence on the stochastic process realization: continuous (risk) and discrete (shock). The authors suggest model errors and residualsas the main source of information for the identification of the probability space of risks. The technique of econometric modeling of the price and return processes on stock market under theconditions of the proposed hypotheses is considered in the empirical part of the study. F-testresults have not disproved the statement that the model residuals provide additional information about the simulated rate in the case of lack of relevant factors.